Methodological Considerations for Content Analysis of Sexual Consent Communication in Mainstream Films. (9th December 2016) - Jozkowski, Kristen N.; Canan, Sasha N.; Rhoads, Kelley; Hunt, Mary
Young adults and college students who receive limited information about certain facets of sexuality, such as how to initiate sex and communicate consent, may turn to television and film for models. In fact, previous research suggests that young adults seek out media content such as television and film to obtain information about sexuality particularly in the absence of other sources of information. As such, it is important to understand the types of actions and behaviors modeled in mainstream media with regard to sexual activity. The overarching goal of the current study was to examine how sexual consent is depicted in mainstream film. However, we found there was limited information to guide the methodological design of such a study. Drawing on previous research, we developed a unique set of analytic procedures for conducting such a specific content analysis. The current article details our methodological approach including (1) how we developed our analytic procedures, (2) our rationale for developing these procedures, and (3) justification for deviating from previous procedures. This article concludes with a discussion regarding limitations of our study and lessons learned for conducting similar studies in the future.